Effects of feeding increasing iron from either iron sulfate or a novel source of dietary iron on growth performance and iron status of nursery pigs - Knobbe, Corinne M.; Williams, Hayden E.; Clark, Anne B.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Dritz, Steven S. (My University, 2017)
A total of 140 pigs (DNA 241×600; initially 12.2 lb BW) were used in a 32-day study to evaluate the effects of increasing added dietary iron from either iron sulfate (FeSO4) or a micronized source of iron (FeCO3; Micronutrients, Inc., Indianapolis, IN) on nursery growth performance and blood criteria. Iron supplementation was withheld in the farrowing house for all pigs to establish iron deficiency. Pigs were weaned at approximately 21 d of age and 5 pigs were allotted to each pen according to gender and BW. Treatments were arranged as a 2×3 + 1 factorial with main effects of iron source (FeSO4 vs. FeCO3) and level (10, 30, or 50 ppm) plus a control diet with no added iron. The basal diet was formulated to contained 40 ppm total dietary iron provided by feed ingredients and was formulated with an iron-free trace mineral premix. Dietary treatments were fed from d 0 to 32 in pelleted form. Pigs and feeders were weighed on d 0, 7, 14, 21, and 32. All pigs were bled via jugular venipuncture and blood was analyzed for hemoglobin and hematocrit. Data was analyzed using PROC GLIMMIX in SAS. No evidence of source by level interactions were observed for any growth or hematological responses. For the overall nursery period (d 0 to 32), ADG, F/G, hemoglobin (Hgb), and hematocrit (Hct) were improved (linear, P<0.05) for pigs fed FeSO4 and FeCO3 compared to the control. There was no evidence of difference (P>0.05) for an iron source effect on blood parameters measured. In conclusion, increasing dietary iron from 0 to 50 ppm from either FeSO4 or FeCO3 improved nursery growth performance and hematological response criteria.
Keywords: Fall 2017